Plasmon-enhanced energy transfer in a hybrid system using silver nanobox array geometries - Bradley, Louise (My University, 2015)
Silver metal nanobox arrays are used to demonstrate plasmon-enhanced non-radiative energy transfer from an InGaN/GaN quantum well to a ~80 nm thick layer of CdSe/ZnS quantum dots embedded in PMMA. Three arrays of varying periodicity are fabricated by helium-ion lithography. Plasmon-enhanced non-radiative energy transfer efficiencies up to 30% are observed from the quantum well to the quantum dots, despite no signatures of non-radiative energy transfer being detected in the absence of the silver nanobox arrays. It is shown that by tuning the Ag nanobox array periodicity the acceptor QD emission can be optimized to benefit from both non-radiative energy transfer and direct plasmonic enhancement of the QD emission.
9th International Congress on Advanced Electromagnetic Materials in Microwaves and Optics (METAMATERIALS)
PUBLISHED
Keywords: Arrays; Energy exchange; Nanostructures; Silver; Quantum dots; Optics; Plasmons